Los gozos del arrabal : la permanencia de objetos rituales y las identidades marginales en el suroriente de Bogotá (2004)
ABSTRACT: The present article tries about the permanence of ritual objects in a context of ritual loss, taking into account the case of “Antigua Fabrica de Loza”, a neighborhood in the south-east of Bogota. This process enables to understand the formulation of marginal identities in areas of the city stigmatized from the colonial period. Also, it makes possible the analysis of a set of pathologies of religion, which evidence deep transformations in the social sections confronted.